Category specificity in early perception: face and word N170 responses differ in both lateralization and habituation properties - Maurer, Urs; Rossion, Bruno; McCandliss, Bruce D. (Frontiers in Human Neuroscience, 2008)
Enhanced N170 ERP responses to both faces and visual words raises questions about category specific processing mechanisms during early perception and their neural basis. Topographic differences across word and face N170s might suggest a form of category specific processing in early perception - the word N170 is consistently left lateralized, while less consistent evidence suggests a right lateralization for the face N170. Additionally, the face N170 shows a reduction in amplitude across consecutive unique faces, a form of habituation that might differ across studies thereby helping to explain inconsistencies in lateralization. This effect remains unexplored for visual words. The current study directly contrasts N170 responses to words and faces within the same subjects, examining both category-level habituation and lateralization effects. ERP responses to a series of different faces and words were collected under two contexts: blocks that alternated faces and words versus pure blocks designed to induce category level habituation. Global and occipito-temporal measures of N170 amplitude demonstrated an interaction between category (word, faces) and block context (alternating, pure). N170 amplitude demonstrated class level habituation for faces but not words. Furthermore, the pure block context diminished the right lateralization of the face N170, potentially pointing to class level habituation as a factor that might drive inconsistencies of right lateralization across different paradigms. No analogous effect for the word N170 was found, suggesting category specificity for this process. Taken together, these topographic and habituation effects suggest distinct forms of perceptual processing drive the face N170 and the visual word form N170.